Purging madness : the politics of mental health in early 20th century colonial Korea - Lim, Yih Ching (Nanyang Technological University, 2022)
This thesis examines the development of mental healthcare in colonial Korea as not merely an evolution of knowledge, but as central elements of biopolitics. The Korean idea of madness underwent a drastic change in the early 20th century. Madness, which was previously deemed as a closed-door family affair, became a societal threat that required institutional intervention. Such a shift in perception played out against the backdrop of the Japanese occupation, the influx of foreign scientific knowledge and the pursuit for modernity. However, the intention of introducing biomedical interpretations of madness was never to enhance the colony’s standard of patient care. It was a governing strategy driven by biopolitical goals and strategically staged as a humanitarian initiative. This thesis argues that the institutionalisation of mental health in colonial Korea was a colonialist imposition intended to strengthen the Japanese rule through ingratiation and it was optimized as a justified means to police the colony effectively. In exploring this new method of policing and coercive control, a new notion of mental illness which connotes threat was cemented in the minds of the Koreans. This lends inconceivable power to the colonial authorities as regulating madness became a necessary evil that claims to safeguard social security and bring modernization to a backward country.